Evaluation of a rapid hydration protocol: Safety and effectiveness. (June 2017) - Meredith, Sean; Hilliard, Jane; Vaillancourt, Regis
Background: The Children's Hospital of Eastern Ontario (CHEO) has implemented a rapid hydration protocol that may reduce the time required to achieve urine specific gravity and pH targets prior to chemotherapy. Objective: The aim of this study was to determine if a rapid hydration protocol resulted in a shorter time to chemotherapy administration and during peak staffing levels without increasing adverse effects. Methods: A retrospective chart review was conducted using data from electronic and paper medical charts, the hematology/oncology whiteboard, and video recordings. Patients who received cyclophosphamide, methotrexate, cisplatin and ifosfamide during the study period were included in the chart review. A urine specific gravity of ≤1.01, and in most cases a urine pH ≥7 was required to begin chemotherapy. Differences in time parameters between the standard and rapid hydration protocols were measured. Comparable parameters included the time from the start of pre-chemotherapy hydration to meeting urine targets, time from starting hydration to administration of chemotherapy, length of hospital stay and the number of chemotherapy administrations that were initiated prior to the nursing shift change at 19:30 h. Results: Data were collected from 116 pre-chemotherapy intravenous hydration events administered to 25 different patients. There was a shorter time required to reach urine specific gravity and pH targets with the rapid hydration protocol compared to the standard hydration protocol, which translated into initiating chemotherapy sooner. There was also a shorter overall length of hospital stay and administration of chemotherapy occurred before the nursing shift change more often in the rapid hydration cohort compared to those patients who received the standard hydration protocol. There were no significant differences in adverse effects between the groups. Conclusion: Patients receiving rapid hydration had a shorter time to chemotherapy administration and had a shorter length of stay in hospital. Rapid hydration resulted in the first dose of chemotherapy being administered earlier when more staff are available, which could reduce errors due to change in hospital personnel. The rapid hydration protocol did not result in an increase in reported adverse effects.